2012
DOI: 10.1002/lt.23467
|View full text |Cite
|
Sign up to set email alerts
|

Invasive fungal infections following liver transplantation: Incidence, risk factors, survival, and impact of fluconazole-resistant Candida parapsilosis (2003-2007)

Abstract: Invasive fungal infections (IFIs) are associated with a high mortality rate for liver transplantation (LT) recipients. To study the incidence of and risk factors for IFIs in LT recipients and the associated mortality rates, we retrospectively reviewed the records of first-time deceased donor LT recipients (January 2003 to December 2007). The incidence of IFIs was 12%. Nonalbicans Candida species accounted for 55% of IFIs; 50% of these IFIs were Candida parapsilosis. Only 43% of Candida isolates were fluconazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
72
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 27 publications
9
72
0
Order By: Relevance
“…and increasing rates of resistance have limited the use of fluconazole. (4) A recent retrospective study at the University of Pittsburgh confirmed that, compared with universal prophylaxis, targeted prophylaxis is effective, feasible, and safe. (26) Therefore, in many transplant groups, prophylaxis targeting Candida spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and increasing rates of resistance have limited the use of fluconazole. (4) A recent retrospective study at the University of Pittsburgh confirmed that, compared with universal prophylaxis, targeted prophylaxis is effective, feasible, and safe. (26) Therefore, in many transplant groups, prophylaxis targeting Candida spp.…”
Section: Discussionmentioning
confidence: 99%
“…(1)(2)(3)(4)(5) Although most IFIs are due to Candida spp., the risk and severity of invasive aspergillosis (IA) in LTRs is well known. (6,7) Universal prophylaxis, mainly with fluconazole, is controversial in patients with a low risk of IFIs.…”
Section: See Editorial On Page 396mentioning
confidence: 99%
“…Invasive fungal infection is associated with high morbidity and mortality in liver transplant recipients, 229,230 with candidiasis, aspergillosis and cryptococcosis respectively being the most common fungal infections. 229 It is important to screen liver transplant candidates, if admitted to the intensive care unit (ICU) pretransplant, for fungal colonization, to determine whether targeted pretransplant or posttransplant antifungal prophylaxis is required.…”
Section: Overimmunosuppression and Infectionmentioning
confidence: 99%
“…229 It is important to screen liver transplant candidates, if admitted to the intensive care unit (ICU) pretransplant, for fungal colonization, to determine whether targeted pretransplant or posttransplant antifungal prophylaxis is required. 230 The improvement of perioperative and postoperative care, modification of immunosuppression, use of prophylactic measures such as trimethoprim-sulfamethoxazole against pneumocystic pneumonia, and fluconazole in high-risk patients waiting for a liver graft in the ICU, have led to a reduction in invasive fungal infections postliver transplant. 205,230 CMV infection is also common postliver transplant.…”
Section: Overimmunosuppression and Infectionmentioning
confidence: 99%
“…As the administration of prophylaxis to all patients undergoing LT is questionable, the most recent guidelines identify high-risk groups, in whom the incidence of FI and IFI is much higher [5]. Furthermore, the use of fluconazole is related to the emergence of mon-Candida spp, as well as fluconazole-resistant species [6]. Also, fluconazole is not active against Aspergillus spp.…”
Section: F Ungal Infections (Fi) Are Infections Caused Bymentioning
confidence: 99%